2017
DOI: 10.1038/s41598-017-06476-6
|View full text |Cite
|
Sign up to set email alerts
|

Anti-asthmatic effect of pitavastatin through aerosol inhalation is associated with CD4+ CD25+ Foxp3+ T cells in an asthma mouse model

Abstract: Statins are competitive inhibitors of 3-hydroxy-3-methylglutaryl-CoA (HMG-A) reductase, and studies have shown that statins also have anti-inflammatory and immunomodulatory properties. The purpose of this study was to investigate the anti-asthmatic effects of pitavastatin, a type of statin, in an asthma mouse model. Mice were sensitized and challenged with ovalbumin (OVA) to establish the asthma model. These mice were then treated with inhaled pitavastatin (5 mg/kg) or dexamethasone (2 mg/kg), the latter of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 48 publications
0
28
1
Order By: Relevance
“…This is inconsistent with some reports that simvastatin can upregulate IL-10 in human subjects with chronic obstructive lung disease (Maneechotesuwan et al, 2015). A limitation of our experiments is that though we observed a suppression of lymphocyte influx with simvastatin therapy, our cytokine array did not include IL-17, which is downregulated by statin treatment in ovalbumin-primed mice (Imamura et al, 2009;Wu et al, 2017). Changes in IL-17 levels could have shed light on the effects of therapy on Th17 / Treg cell balance as a mechanism for Treg-associated suppression of Th2 cell-mediated inflammation.…”
Section: Figurecontrasting
confidence: 99%
See 2 more Smart Citations
“…This is inconsistent with some reports that simvastatin can upregulate IL-10 in human subjects with chronic obstructive lung disease (Maneechotesuwan et al, 2015). A limitation of our experiments is that though we observed a suppression of lymphocyte influx with simvastatin therapy, our cytokine array did not include IL-17, which is downregulated by statin treatment in ovalbumin-primed mice (Imamura et al, 2009;Wu et al, 2017). Changes in IL-17 levels could have shed light on the effects of therapy on Th17 / Treg cell balance as a mechanism for Treg-associated suppression of Th2 cell-mediated inflammation.…”
Section: Figurecontrasting
confidence: 99%
“…Another mechanism for limiting accumulation of simvastatin is the presence of the simvastatin metabolizing enzyme, CYP3A11 in mouse lung (CYP3A4 in humans) (Haag et al, ; Biggs et al, ; Li et al, ; Shah et al, ). Recent evidence indicates that direct delivery of statins to the lung may be needed to reverse airway hyperreactivity and hypersensitivity (Zeki et al, ; Wu et al, ). Thus our evidence indicated that systemic administration of simvastatin was not able to mitigate airway dysfunction, despite its capacity to prevent immune cell influx and release of pro‐inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the present uncertainty regarding the use of statins in asthma, we and others began investigating the safety and efficacy of delivering statins via inhalation in animal models, as an alternative approach to orally administered statins [100–102,104,105,128–130]. We are currently designing studies using mass spectrometry to measure concentrations of statins and their active metabolites in the plasma, airways, and lungs of patients ingesting oral statins.…”
Section: Rationale For Developing Inhaled Statinsmentioning
confidence: 99%
“…The mice were subsequently challenged with aerosolized PBS (baseline) acetylcholine treatment doses of 0, 1, 2, 4, 8, and 16 mg/mL. Average compliance values were recorded during a 3 min period following each challenge [19].…”
Section: Measurement Of Airway Resistancementioning
confidence: 99%